RELATIONSHIP BETWEEN CANDIDATE SELECTION AND CONTRACT AWARD AND SERVICE DELIVERY. A DESCRIPTIVE CROSS-SECTIONAL SURVEY IN KABALE DISTRICT LOCAL GOVERNMENT. - Mercy Atuheire; Edmand Bakashaba; Muhammad Sendagi (Student's Journal of Health Research, 2023)
Background. This study aims to determine the relationship between candidate selection & contract award and service delivery in Kabale District Local Government. Methodology. This study employed descriptive, correlational, and cross-sectional survey design. The study further adopted a mixed approach whereby both qualitative and quantitative techniques were used to analyze the data to reach a logical conclusion about the findings. A target population of 85 respondents was used from which 70 respondents were selected. Data was collected using questionnaires and interviews and analyzed using SPSS.  Results. The correlation between candidate selection and contract award and service delivery was 0.356 with a significance value of 0.000. The findings revealed that 87.7% of the respondents agree that the experience of the candidates is essential in selecting candidates to provide quality services, the study findings showed that during candidate selection, the academic qualifications of the contractors are considerable to ascertain the skills and knowledge of contractors in performing given tasks, the experience of the candidates is essential in selecting candidates because it helps to select contractors with knowledge and with ability to provide quality services, contract award are based on democratic vote by Procurement committee members of Kabale District Local government hence candidates with good marks based on members ranks are recommended the best for the job. Conclusion. There was a positive significant relationship between the candidate selection and contract award and service delivery in Kabale district local government. This means that the candidate selection and contract award are an integral part of the contract award process and service delivery in the Kabale district local government.  Recommendation. The Kabale district local government council should also ensure that candidates provide additional information on performance, experience, academic qualifications, and financial statements as this will help them to ensure quality services are provided on time.